Vasopressin and oxytocin release during prolonged environmental hypoxia in the rat. Issue 1 (January 1997) - Kelestimur, H; Leach, R M; Ward, J P; Forsling, M L
Abstract : BACKGROUND: The mechanism causing peripheral oedema in hypoxaemic chronic obstructive pulmonary disease has not been established. Vasopressin, a powerful antidiuretic hormone involved in salt and water homeostasis, is released in response to acute hypoxia. However, the effect of prolonged hypoxaemia on hypothalamic and pituitary release of the magnocellular hypothalamic hormones, vasopressin and oxytocin, has not previously been studied. METHODS: Male Wistar rats were randomly allocated to either normobaric, hypoxic (10% O2) or control (21% O2) environmental chambers. An initial series of experiments examined plasma vasopressin concentration, osmolality, sodium concentration, packed cell volume (PCV), and weight gain at weekly intervals (n = 4-6) for six weeks. The maximum increase in plasma vasopressin concentration and PCV occurred after five weeks. In a second experiment vasopressin and oxytocin concentrations in the hypothalamus, pituitary gland, and plasma were measured in eight control and eight hypoxic rats after five weeks in the environmental chambers. RESULTS: In rats exposed to environmental hypoxia PCV increased (p < 0.001) and weight gain decreased (p < 0.05) compared with controls. The plasma vasopressin concentration increased progressively from a baseline of 1.36 (0.2) pmol/l (n = 6) to a maximum of 4.38 (0.8) pmol/l (n = 6; p < 0.01) during the first five weeks of environmental hypoxia (difference 3.02 (95% CI 1.18 to 4.86)). Plasma osmolality and sodium concentration were unchanged in hypoxic rats compared with controls during the six week period. The hypothalamic vasopressin concentration was increased (p < 0.001) after five weeks of environmental hypoxia (91.6 (4.8) pmol/ hypothalamus) compared with controls (57.4 (5.1) pmol/hypothalamus), the difference being 34.2 pmol/hypothalamus (95% CI 21.6 to 46.5). The pituitary vasopressin concentration was unchanged. In hypoxic rats hypothalamic oxytocin (59.6 (3.2) pmol/hypothalamus) was greater (p < 0.01) than in controls (42 (3.8) pmol/hypothalamus), a difference of 17.6 pmol/ hypothalamus (95% CI 8.7 to 26.5). Similarly, the plasma oxytocin concentration was increased (p < 0.05) in hypoxic rats (6.78 (1.2) pmol/l) compared with controls (3.3 (0.8) pmol/l), a difference of 3.48 pmol/l (95% CI 0.89 to 6.07). The pituitary oxytocin concentration was unchanged in the two groups. CONCLUSIONS: These results demonstrate an increase in hypothalamic production of vasopressin and oxytocin in rats during prolonged hypoxaemia. Increased plasma concentrations of neurohypophysial hormones would be expected to impair sodium and water homeostasis in patients with hypoxaemia. However, the absence of change in the plasma osmolality and sodium concentrations in this study and previous clinical investigations suggests that compensatory mechanisms modulate the actions of both vasopressin and oxytocin. A reduction in renal blood flow or decreased renal responsiveness to the neurohypophyseal hormones may be involved.